Is polaron effect important for resonant Raman scattering in self-assembled quantum dots? - Vasilevskiy, Mikhail (2005)
While the diagonal (or intra-level) interaction of a confined exciton with optical phonons in selfassembled quantum dots (SAQD’s) is rather weak, the non-diagonal one can lead to a considerable change of the exciton spectrum and the formation of a polaron. An impact of this effect on resonant inelastic light scattering is studied theoretically. The polaron spectrum is obtained by numerical diagonalisation of the exciton–phonon interaction Hamiltonian in a truncated Hilbert space of the non-interacting excitons and phonons. Based on this spectrum, the probability of the multi-phonon Raman scattering is calculated, which is compared to that obtained within the standard perturbation theory approach (where phonon emission and absorption are irreversible). It is shown that there are two major effects of the polaron formation: (i) the intensity of the two-phonon (2 LO) peak, relative to that of the fundamental 1 LO one is strongly increased and (ii) the resonant behaviour of the 1 LO peak differs considerably from the perturbation theory predictions. With the correct theoretical interpretation, resonant Raman scattering in SAQD’s opens the possibility of accessing the (renormalised) exciton spectrum and exciton–phonon coupling constants